The lost girls : three friends, four continents, one unconventional detour around the world - Baggett, Jennifer (HarperCollins, 2010)
"Unable to gain perspective in fast-paced Manhattan, three twentysomethings quit their coveted media jobs and leave behind their friends, boyfriends, and everything familiar to travel the globe. Dubbing themselves the Lost Girls, they embark on an epic yearlong search for inspiration and direction. This candid and compelling memoir will speak to anyone who has ever felt the desire to spread her wings and discover the world with her best friends by her side"--Publisher description.